Aspectos psicológicos de la astenia - Gónzalez Barón, Manuel; Ordóñez, Amalio; Lacasta, María Antonia; Calvo, Cristóbal (Psicooncología, 2004)
The asthenia is a frequent symptom in the patients with cancer and has important repercussions on its quality of life. In this article east problem is approached from a psychological perspective, basing on empirical data and theoretical and scientific approaches to us of the field of psychology, with the purpose of obtaining a greater knowledge of this multifactorial phenomenon to be able to help as far as possible to confront better east form problem to multidiscipline and to diminish the suffering that can produce the in the patients with cancer. One concludes that the present boarding front to the disease emphasizes the necessity to conserve the habitual activities at a level adapted without causing frustration. The rest and lack of physical activity, like answer to the fatigue, they can (separately or jointly) induce or increase the asthenia. It is not only necessary to investigate in symptoms like the depression, the pain, or the asthenia of independent form, but also jointly; an effective treatment of the depression can alleviate the asthenia, but inversely the suitable treatment of pain can increase the asthenia. It is necessary to establish a measurement instrument that is valid, trustworthy, sensible to the changes, with that the different professionals we pruned to compare results.